Determining Roles of Cu0 in the Chemosynthesis of Diols via Condensed Diester Hydrogenation on Cu/SiO2 Catalyst. Issue 15 (9th June 2020) - Wang, Weichao; Wang, Hui; Zhang, Jingwei; Kong, Lingxin; Huang, Huijiang; Liu, Wei; Wang, Shengping; Ma, Xinbin; Zhao, Yujun
Abstract: Copper‐based catalyst was applied in the condensed diester hydrogenation with unexpected high selectivity (∼100 %) to 1, 6‐hexanediol. On basis of the mass transfer analysis and kinetics results, the reaction rate of the condensed diester hydrogenation was deduced to be controlled by the activation of hydrogen on Cu 0 sites, which was further demonstrated by the correlations between the catalytic activity and different copper species. Importantly, this catalysis mechanism is different with that of gas‐phase diester hydrogenation, which is generally determined by the adsorption of ester on Cu + species. Abstract : Cu/SiO2 Catalyst : A significantly high hexanediol selectivity of 100 % is achieved in the condensed diester hydrogenation on Cu/SiO2 catalyst. The determining‐step of this system is the activation of hydrogen on Cu 0 sites, which is different with that in gas‐phase hydrogenation of diesters.